SOCIAL PROCESSES IN THE AGE OF DIGITAL TRANSFORMATION: A PHILOSOPHICO-LEGAL ANALYSIS - Sitora Abdusattarova (Journal Park Publishing, 2025)
This article investigates the nature and dynamics of social processes through the lens of philosophical and legal analysis, with a particular focus on digital transformation. Drawing on classical and contemporary theories—from Herbert Spencer to Anthony Giddens and Manuel Castells—the paper conceptualizes social processes as multi-level, nonlinear, and normatively regulated phenomena. The study highlights the role of law not only as a regulatory framework but also as an active agent of social modeling in an increasingly digital environment. It proposes an integrated analytical approach that considers the interaction between individuals, institutions, and digital technologies in shaping social change.